Investigation Of Dynamic Failure Mechanism Of Kenaf Composite Using Sem - Fadzieli, Nur Liyana Mohamad (Universiti Sains Malaysia, 2017)
The dynamic tests were carried out by using Split Hopkinson Pressure Bar (SHPB) apparatus. The test were conducted on Kenaf composite at strain rates of 872